Comparison of the Effect of Competency-Based Education Model and Traditional Teaching on Cognitive and Clinical Skills Learning among ICU Nursing Students - Azam Naderi; Rahim Baghaei; Yousef Mohammad por; Nasrin Aliramaei; Kobra Ghorban zadeh (مجله ایرانی آموزش در علوم پزشکی, 2012)
Introduction: Clinical education and evaluation is fundamental to nursing education. This study investigated the effect of competency-based and traditional teaching methods on clinical and cognitive learning of nursing students. Methods: This quasi-experimental study was done on 28 nursing students taking ICU courses in the academic hospital of Taleghani affiliated with Urmia Medical University in 2010 and 2011.Subject were selected by using census sampling and then using simple randomization method and assigned to experiment and control groups. Both groups took pre and post tests for cognitive skills through answering a questionnaire and the post test for clinical skills was done through a check list. Data were analyzed using descriptive and analytical statistical tests and SPSS 16. Results: The results showed the mean and standard deviation scores in clinical skills obtained from the experiment group students (competency-based education) and control (traditional training)were 162±10/72and117±25/01,which were significantly greater in the experimental group (p< 0/05). Also the independent t-test on pretest scores on cognitive skills showed there was not a statistically significant difference between the two groups (p>0/05). But post-test scores on cognitive skills in the experiment group were significantly higher than those of the control group (P<0.05). Conclusion: The results showed that the application of competency-based teaching method over traditional methods provides the opportunity to improve the learning of clinical and cognitive skills in nursing students. It is suggested that this method be used in teaching nursing students for training and evaluation